New and Renewable Energy Optimization to Meet North Sumatera Province’s Energy Share and Emission Road Map Period Year of 2022-2025 by Using LEAP - Dedi Khairunas; Hadiyanto Hadiyanto; Sri Widodo Agung Sueda (Department of Mechanical Engineering, Universitas Andalas, 2023)
The objective of this work is to evaluate the long-term energy demand and supply in North Sumatera Province. The Road Map for both NRE energy shares and GHG Emissions in North Sumatera is in Regional Regulation No. 4 Year 2022. The growth of electricity demand, type of power generation determination and transmission/distribution losses will be defined into two main scenarios: Business As Usual (BAU) and Policy (KEB), and eight sub scenarios to assess possibilities to reach the Road Map during period of 2022-2050. Four scenarios under BAU Scenario show that the percentage of NRE energy shares and GHG Emissions are achievable during period of 2022-2025. The range of NRE shares is 45.1% up to 96.2%, and GHG Emissions production range is 3% - 30% from the Road Map. Meanwhile, Four scenarios under KEB Scenario show that the percentage of NRE energy shares and GHG Emissions are achievable during period of 2022-2025. The range of NRE shares is 44% up to 93.4%, and GHG Emissions production range is 4% - 30% from the Road Map. Some scenarios under BAU gives slightly higher NRE shares and GHG Emissions production saving since the higher growth of demand in BAU Scenarios is possible for more NRE power generation capacity in operation.